2010 IEEE International Conference on Computational Photography (ICCP) 2010
DOI: 10.1109/iccphot.2010.5585098
|View full text |Cite
|
Sign up to set email alerts
|

Transfer efficiency and depth invariance in computational cameras

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…6(b), the MTF is oscillating, reaching maxima at s = n∆s and minima at s = (n+1/2)∆s for integer n (Table II(a) shows n = 0 case). The oscillation amplitude becomes larger for higher frequencies, which was also observed in [Baek 2010], meaning that MTF invariance is low. The average MTF is shown to be around…”
Section: Mtf Invariance Integration Surface Integration Windowsupporting
confidence: 51%
See 3 more Smart Citations
“…6(b), the MTF is oscillating, reaching maxima at s = n∆s and minima at s = (n+1/2)∆s for integer n (Table II(a) shows n = 0 case). The oscillation amplitude becomes larger for higher frequencies, which was also observed in [Baek 2010], meaning that MTF invariance is low. The average MTF is shown to be around…”
Section: Mtf Invariance Integration Surface Integration Windowsupporting
confidence: 51%
“…This paper builds upon the previous analyses of computational cameras in relation to light field capture and rendering [Ng 2005;Levin and Durand 2010], depth of field extension Hasinoff et al 2009a;Baek 2010] and motion deblurring Cho et al 2010;Bando et al 2011].…”
Section: Theoretical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Baek compared the degree of depth-invariance of these two techniques, and observed that focal sweep gives a near-optimal tradeoff between MTF and depth-invariance at all frequencies [Baek 2010], while wavefront coding is only guaranteed to be optimal at a single frequency. We introduce a new diffusion coding camera that produces near identical performance to focal sweep, but without the need for moving parts (see Figures 1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%